Nilai-nilai Seni Metetuasan Pada Banten Prayascita - Ni Komang Wiasti (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2023)
Banten purification is a means to harmonize human life. Such as Banten Prayascita which functions as a purification of Bhuana Agung and Bhuana Alit which is used in every Panca Yadnya ceremony. These facilities have artistic value in making or arranging their components in order to realize ritual facilities that are sacred and magical. The research method used is descriptive qualitative research to analyze and examine the value of metetuasan art in Banten Prayascita consisting of: (1) Tattwa values are very deep because the tetuas are in the form of images of human organs such as eyes, hair and various plants as well as symbols of the Gods. ; (2) The ethical value is the procedure for offering the Banten Prayascita if it is presented to the priest and to humans by using a puja mantra and its elemental components are neatly arranged; (3) The value of the ceremony that Banten Prayascita is used at the Panca Yadnya ceremony as a means of concentration and means satyam siwam, Sundaram